Delineation of the Cardioprotective Agents found in red wine - Lamont, Kim (Department of Medicine, 2014)
Secondary leach concentrate (SLC) is an important bleed stream for minor elements from Anglo Platinum's Base Metal Refinery (BMR) which produces copper nickel and cobalt sulphate. It contains mainly sulphur, iron jarosites, unleached base metals and platinum group metals (PGMs), which makes the treatment of SLC necessary. The SLC is currently toll-refined at Umicore's Hoboken smelter and refinery to recover revenue from entrapped valuable metals. This method of treatment results in excessively high costs due to high transport and toll refining expenses as well as penalties. Thus, an in-house method of treatment by Anglo Platinum itself would prove beneficial in that it would eliminate these excessive costs and also provide a method of treatment in the event of residues exporting becoming banned or strongly penalised in future. Therefore, a method for treating SLC in-house is investigated. The first stage of the proposed treatment method involves a pyrometallurgical process where the removal of amphoterics by oxidative fuming, followed by reduction to recover base metals from the slag takes place. The PGMs are reported mainly to the metal alloy phase along with the base metals during this process. The project discussed in this report deals with the treatment of this furnace alloy which is referred to as Cu alloy. The Cu alloy is used to produce anodes to be applied to an electrorefining application for the recovery of Cu as a Cu cathode and PGMs in the form of anode slimes. Spent electrolyte from the BMR copper electrowinning section adjusted to specific pH and Cu concentration is used as electrolyte to which dissolvable metals (such as Ni and Fe) are recovered. The purpose of the process is to recover PGMs to anode slimes with a composition suitable to be blended with the final concentrate that is sent to the Precious Metals Refinery (PMR). The performance of this process on the Cu alloy provided is investigated and the anode slimes produced are characterised in order to propose further methods of purification before blending with PMR feed. The typical energy consumption, cathodic current efficiency, anodic copper dissolution rate and deportment of elements (especially PGMs) are determined. The effects of various operating parameters on the performance are also investigated in order to propose operating conditions. The operating parameters that are investigated are current density, Cu and H2SO4 concentrations in electrolyte and the use of an additive. A preliminary process design based on knowledge and experience gained during the literature review and test work is given. -PAGE 3 OF 181 The major technical factors in electrorefining are the cathode purity, the production rate and the specific energy consumption. These factors are influenced primarily by anode quality, electrolyte conditions and cathode current density. Design considerations and typical design parameters for other industrial Cu electrorefining applications are studied as well as possible further treatment of anode slimes for the concentration of PGMs. A total of eleven experiments were performed with a variety combinations of Cu concentration (30, 40 and 50 g/l), H2SO4 concentration (110, 130, 160 and 190 g/l) and current density (100, 125, 150, 250, 300 A/m2). In each experiment only one parameter was changed while all others were kept constant at the base-case setting of 40 g/l Cu, 160 g/l H2SO4, and 125 A/m2. The testwork showed that electrolytic refining of the Cu alloy, produced by a two stage pyrometallurgical treatment of current SLC, produces a highly concentrated PGM residue at an overall SLC mass reduction of 99.3%, with excellent PGM recovery to the anode slimes material. The different operating parameters that were tested successfully, all showed very good repeatability and greater than 99% PGM recovery from the Cu alloy, which would result in an overall recovery of 98% from SLC. Very little or none of the base metals that were supplied by the anode or the electrolyte feed reported to the anode slimes. The typical operating conditions (cell potential, current efficiency, anodic Cu dissolution and element deportment) that were observed correlated well with literature and the theoretically calculated values. The characteristics of the anode slimes produced stayed relatively similar throughout the different operating parameters and strong confidence can be placed in the production thereof and the recovery of the PGMs. The characteristics of the spent electrolyte and the Cu cathodes were also found to be suitable for integration in the BMR circuit. The anode slimes composition was 20 to 30% PGMs, 20 to 30% base metals, 15 to 20% Ag, As, Te, Se, Pb and 2 to 5% Al, Si, Sb, Bi, Zn and Sn. The blending of these slimes with typical PMR feed will result in a new PMR feed where the Pt grade of the feed to PMR is reduced by 4 to 5.5%, the Cu grade increased by 2 to 4% and the Ni content reduced by +-4%. Other concerns are the increase of As, Te, and Pb by between 0.5 and 1%. -PAGE 4 OF 181 The PGM-rich (<60%) phase in the anode slimes is a mostly amorphous matrix phase containing mostly palladium and other PGMs, arsenic and tellurium [Pd73As6Te21] with small amounts of Cu. Anode slimes produced from electrorefining can either be subjected to an additional process step to remove Ag, Pb and base metals before it is blended with the final concentrate (FICO) as feed for PMR, or it can be sent to the metallics section in PMR which includes a roast and a leach stage. The treatment of the anode slimes depends on the nature of the slimes. A preliminary process design was performed with proposed design parameters of electrolyte concentrations of 40 g/l Cu and 160 g/l H2SO4 at 65 deg C and a current density of 200 A/m2. The process consists out of seven cells in series with 55 anode cathode pairs in parallel per cell. The process has a maximum capacity of 127 t/m of anode material which allows 56 days of downtime per year if the current SLC produced (6600 t/a) is treated. The maximum capacity for Cu production is 1349 t/a and anode slimes 50.3 t/m. The power consumption per kg of anode dissolved will be 0.175 kWh/kg.